Emergence of IMP-8-Producing Comamonas thiooxydans Causing Urinary Tract Infection in China - Guo, Xiaobing; Wang, Qian; Xu, Hao; He, Xiaohong; Guo, Lihua; Liu, Shuxiu; Wen, Peipei; Gou, Jianjun (Frontiers in Microbiology, 2021)
The emergence of carbapenem resistance (CR) caused by hydrolytic enzymes called carbapenemases has become a major concern worldwide. So far, carbapenem resistance genes have been widely detected in various bacteria. However, there is no report of carbapenem resistance gene harboring Comamonas thiooxydans. We first isolated a strain of an IMP-8-producing C. thiooxydans from a patient with urinary tract infection in China. Species identity was determined using MALDI-TOF MS analysis and carbapenemase-encoding genes were detected using PCR. The complete genomic sequence of C. thiooxydans was identified using Illumina Novaseq and Oxford Nanopore PromethION. Antimicrobial susceptibility analysis indicated that the C. thiooxydans strain ZDHYF418 was susceptible to imipenem, intermediate to meropenem, and was resistant to aztreonam, fluoroquinolones and aminoglycosides. The blaIMP-8 gene was chromosomally located, and was part of a Tn402-like class 1 integron characterized by the following structure: DDE-type integrase/transposase/recombinase-tniB-tniQ-recombinase family protein-aac(6’)-Ib-cr-blaIMP-8-intI1. Phylogenetic analysis demonstrated that the closest relative of ZDHYF418 is C. thiooxydans QYY (accession number: CP053920.1). We detected 330 SNP differences between ZDHYF418 and C. thiooxydans QYY. Strain QYY was isolated from activated sludge in Jilin province, China in 2015. In summary, we isolated a strain of C. thiooxydans that is able to produce IMP-8 and a novel blaOXA. This is the first time that a carbapenem resistance gene has been identified in C. thiooxydans. The occurrence of the strain needs to be closely monitored.